Research of the Calculation Method of the Gear Time-varying Mesh Stiffness based on FEM - Zhang Bobo; Cai Li; Fang Jie; Zheng Yuan; Wang Tao; Xiong Yangshou (Jixie chuandong)
At present，the formula for calculating time-varying meshing stiffness of gears is often simplified according to the ISO experimental values. This method cannot accurately reflect the comprehensive characteristics of the meshing stiffness of different gears. Aiming at this problem, by using the APDL, a parametric finite element model of involute spur gear is established. The contact displacement of the gear tooth is obtained by contact analysis and the stiffness is calculated. The effect of rim thickness on stiffness is considered. The spur gear single tooth stiffness formula is obtained by least square method and the time-varying mesh stiffness formula of any tooth number meshing is derived. By comparing with the Ishikawa formula, potential energy method, Kuang method, the advantages and disadvantages of each calculation method in calculating the time-varying stiffness are illustrated. The results of FEA formula and ISO are compared to verify the reliability of the results.